Normative data for healthy elderly on the phonemic verbal fluency task - FAS - Thais Helena Machado (Dementia & Neuropsychologia, 2009)
Phonemic verbal fluency tests assess the poduction of words beining with specific letters. Of these letters, the most frequently used are F, A and S. It is a sensitive test for assessing frontal lobe functions. Objective: To provide normative data for the elderly Brazilian population on the FAS test and to investigate the effects of age and schooling on test performance. Methods: The individuals were divided into three age groups (60–69, 70–79 and ≥80 years), and into four groups according to education (1–3, 4–7, 8–11 and ≥12 years). All subjects were assessed by the Mini Mental State Examination and the FAS. Data were analyzed with Student’s t test, ANOVA, simple linear regression and Spearman’s correlation. Results: We evaluated 345 cognitively healthy volunteers, 66.66% being female, aged 60 to 93 years, with an educational level ranging from one to 24 years. The average (number of items) ±SD for the whole sample was 28.28±11.53. No significant effect of gender was observed (p=0.5). Performance on the MMSE and education exerted a direct influence on FAS scores (p<0.001), with education being the most significant factor. A positive correlation was found between FAS and the MMSE (r=0.404; p<0.001). Conclusion: The performance of Brazilian elderly on the phonemic verbal fluency tests-FAS is significantly influenced by education, where individuals with higher educational level present better performance than those with fewer years of schooling. Age and gender did not prove significant with the FAS.